Locale Matters: Regional Needs of U.S. Military Service Members and Veterans. (15th September 2022) - Cacace, Sam; Smith, Emily; Desmarais, Sarah; Alders, Elizabeth
Abstract: Military service members (MSM) and veterans make up nearly 10% of the U.S. population. They face unique challenges and require unique assistance related to community services and resources. However, little has been done to determine the specific needs within this population, particularly with regard to "locale" or "geographically-specific" military population needs. This study used a mixed-methods approach to investigate geographically-specific needs in the MSM and veteran populations residing in one southeastern state, collecting both qualitative focus group data and secondary quantitative data. The qualitative data was gathered from focus groups (15 veterans and leaders from military-service organizations) and the quantitative data was gathered from client requests from a regional network of military and veteran-serving organizations (N = 4, 328). Thematic analysis of focus group transcripts shows, from the organizational side, a lack of availability, understanding, education, and advertising of resources. The client call data showed that MSM and veterans who live in higher population locales were more likely to experience longer wait times to achieve needs resolution when compared to the smaller locale group ( β = 0.0000606, t (4, 226) = 14.49, p < .0001, R 2 = 0.047). Follow-up investigations should examine the importance of regional differences in professional branding and information dissemination practices maintained by organizations serving the MSM and veteran populations in this locale, with the goal of finding how to communicate more effectively and efficiently with their target audience(s). These future efforts should include comparing data with other regions and national data sets to further understand locale specific needs.